Объяснение:
SnO + 2HCl = SnCl2 + H2O
SnO + 2H(+) + 2Cl(-) = Sn(2+) + 2Cl(-) + H2O
SnO + 2H(+) = Sn(2+) + H2O
SnCl2 + 2NaOH = Sn(OH)2↓ + 2NaCl
Sn(2+) + 2Cl(-) + 2Na(+) + 2OH(-) = Sn(OH)2↓ + 2Na(+) + 2Cl(-)
Sn(2+) + 2OH(-) = Sn(OH)2↓
Sn(OH)2 + H2SO4 = SnSO4 + 2H2O
Sn(OH)2 + 2H(+) + SO4(2-) = Sn(2+) + SO4(2-) + 2H2O
Sn(OH)2 + 2H(+) = Sn(2+) + 2H2O
SnSO4 + BaCl2 = BaSO4↓ + SnCl2
Sn(2+)+ SO4(2-) + Ba(2+) + 2Cl(-) = BaSO4 ↓+ Sn(2+) + 2Cl(-)
Ba(2+) + SO4(2-) = BaSO4↓
BaSO4 + 2NaOH = Ba(OH)2 + Na2SO4
BaSO4 + 2Na(+) + 2OH(-) = Ba(2+) + 2OH(-) + 2Na(+) + SO4(2-)
BaSO4 = Ba(2+) + SO4(2-)
27,3 г Х л
2K + H2SO4 = K2SO4 + H2
n=2 моль n=1 моль
М = 39 г/моль Vm=22,4 л/моль
m=78 г V = 22,4 л
27,3 г К - Х л Н2
78 г К - 22,4 л Н2
V(H2) =27,3 * 22,4 / 78 =7,84 л